Cutaneous Pili Migrans: A Case Report - Kawina Ingkapairoj (2020)
© 2019 S. Karger AG, Basel. All rights reserved. Hair-induced creeping eruption is a rare condition characterized by a fragment of hair embedded in the superficial layer of the skin. Mainly cases from Asia are reported. We report a 39-year-old Thai female who experienced painful blackish linear eruption on the right side of the neck. The proximal end of the lesion was excised, and the rest of it was removed using forceps. The lesion suddenly disappeared. The black line that was removed from the lesion appeared to be hair. In conclusion, this condition is important and should be considered when patients present with creeping eruption.